1984
DOI: 10.1159/000233457
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis, in vivo, of Immune Complexes by Dendritic Cells in the Lymph of Sheep

Abstract: Although the occurrence of dendritic, macrophage-like cells in the peripheral lymph of sheep, pigs, rabbits, and man is well documented, the exact nature of these cells has become controversial. Generally, such cells tend not to adhere firmly to glass or exhibit phagocytosis in in vitro systems. However, when immunized sheep were given a subcutaneous injection of specific antigen (horseradish peroxidase), most of the macrophage-like cells in the lymph from the injection site could be shown by transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…A second possibility is that DC bind antigen via cytophilic immunoglobulin or via uptake of antigedantibody complexes. Recent independent studies in sheep [7,26], have confirmed earlier observations [28] that afferent lymph DC bear surface IgM and IgG molecules, and can take up immune complexes [29].…”
Section: Discussionsupporting
confidence: 65%
“…A second possibility is that DC bind antigen via cytophilic immunoglobulin or via uptake of antigedantibody complexes. Recent independent studies in sheep [7,26], have confirmed earlier observations [28] that afferent lymph DC bear surface IgM and IgG molecules, and can take up immune complexes [29].…”
Section: Discussionsupporting
confidence: 65%
“…Skin paint- ing with FITC induced a population of DC in the draining lymph node capable of sensitizing antigen-specific T cells and inducing sensitivity in naive recipients [8]. D C migration is not exclusively restricted to skin versus skinassociated lymph nodes, but actively functions between other tissues [22], such as intestine and MLN, as observed by Liu and MacPherson [23, 241. These investigators, using mesenteric lymphadenectomy in the rat, clearly demonstrated that intestinal DC migrated from the gut to distant lymphoid organs.…”
Section: Development Of Potent Immunostimulatory DC Upon Stimulation mentioning
confidence: 99%
“…Studies on peripheral lymph draining from several body regions of sheep have established that the extent of lymphocyte recirculation is lower in nonlymphoid tissues than in lymphoid, and that peri pheral lymph typically contains 5-20% of macro phages and so-called 'veiled' cells, most of which have the ability to engulf immune complexes in vivo [1,2].…”
mentioning
confidence: 99%